Common weeds of Guyana - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Common weeds of Guyana by Aung Myint 1994 271pp US$22.25 Dr B Ford, National Agricultural Research Institute, Mon Repos East Coast Demerara, GUYANA